Optimization of performance, emission, friction and wear characteristics of palm and Calophyllum inophyllum biodiesel blends. (15th June 2016) - Mosarof, M.H.; Kalam, M.A.; Masjuki, H.H.; Alabdulkarem, Abdullah; Ashraful, A.M.; Arslan, A.; Rashedul, H.K.; Monirul, I.M.
Highlights: All of biodiesel blends were given higher BSFC than diesel fuel, except for CIB10. Diesel produces higher BP and BTE as compared to PB and CIB blends. CO and HC emissions of PB blends were reduced more than diesel and CIB blends. PB blends contained lower metal compositions compared to diesel and CIB blends. PB20 showed lower worn scar surfaces area compared to diesel and biodiesel blends. Abstract: A running automobile engine produces more friction and wear between its sliding components than an idle one, and thus requires lubrication to reduce this frictional effect. Biodiesel is an alternative diesel fuel that is produced from renewable resources. Energy studies conducted over the last two decades focused on solutions to problems of rising fossil fuel price, increasing dependency on foreign energy sources, and worsening environmental concerns. Palm oil biodiesel is mostly used in Malaysia. This study conducted engine performance and emission tests with a single-cylinder diesel engine fueled with palm and Calophyllum inophyllum biodiesel blends (PB10, PB20, PB30, CIB10, CIB20, and CIB30) at a full-load engine speed range of 1000–2400 rpm, and then compared the results with those of diesel fuel. Friction and wear tests were conducted using the four-ball tester with different temperatures at 40 and 80 kg load conditions and a constant speed of 1800 rpm. The average brake specific fuel consumption increased from 7.96% to 10.15% while operating on 10%, 20%, and 30% blends of palm and C. inophyllum biodiesel. The respective average brake powers for PB20 and PB30 were 9.31% and 12.93% lower compared with that for diesel fuel. PB20 produced relatively lower CO and HC emissions than the diesel and biodiesel blends. Diesel produced low amounts of NOX emission, and the CIB blend produced a lower frictional coefficient compared with the diesel and PB blends. PB30 showed high average FTP and low average WSD, both of which enhanced lubricating performance. An average metal element composition was found in PB20 under the 40 and 80 kg load conditions. PB20 showed lower worn scar surface areas compared with the diesel and biodiesel blends. Results indicated that PB20 has better engine performance, lower emission, and good lubrication properties compared with diesel and biodiesel blends. Thus, PB20 is suitable for use in diesel engines without the need for any engine modification.